Explosives & Accessories Used in the Isthmus of Mexico to Break Up & Fissured the Lime/Stone/Sulphur Strata - Antonio S. Aldana Selders (International Society of Explosives Engineers, 1995)
With special designed explosive and a system to lower down a heavy load of Explosives through 8" pipe results are achieved, the stimulation of sulphur production takes place. Well # 18-1063 at 515 meters below ground is loaded with 802 units of explosives with total weight of 1820 kilos to fill up the column of 93 meters of limestone & sulphur strata.